Direction of technical and tactical skill in athletes playing team sports, playing with light position - Doroshenko Eduard Iur'evich (Kharkov National Pedagogical University, 2011)
A new method for evaluating the effectiveness of technical and tactical activities in basketball. A distinctive feature of the technique is presented key components of the accounting games, length of stay in the athletes play and the specific features of the game line. Established the specific means of correction of the training process taking into account the magnitude and direction of the load. Identified ways of solving the problem of optimal evaluation of gaming activities, taking into account the length of stay player on the court and its role. Refine management training process in team sports.